Eight Grade Students' Speaking Achievement and Perception of Using Spying Method - Hengki Ripaldi; Nike Angraini; Dita Rizki Anggraini; Dio Resta Permana (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This research was based on students’ English speaking achievement at school during the 2024/2025 academic year, thus the students’ English speaking achievement was pathetic. Speaking is very important in language learning because it helps students acquire the target language and academic content. English teachers try to use the spying method to help students improve their speaking skills. The spying method uses spies to gather information, in order to support and increase students' confidence in their English language skills Thus, the objectives of this study were to find out: (1) significant improvement in speaking skills using or not using the Spying method and (2) whether there were significant mean difference between the students’ who are taught.. Quasi-experiment research was used in this study. There were 69 students as a sample, 35 students for the experimental class and 34 students for the control class. The data were collected using a speaking test. Data were analyzed using paired sample t-test and independent sample t-test. Based on data analysis, it was found that there was a significant increase in students' speaking skills. Before being proven by the t- test results of the paired sample with the t-test obtained (-26.998) and the significance value (0.00) was lower than α (0.05). That shows that students' speaking skills have been improved. In addition, the independent sample t-test results show that the obtained t-test (12.342) and significant value (<.001) was lower than α (0.05). The results shows significant mean difference in students' speaking achievement between students who were taught by using spying method and those who were not taught.